Evaluación del uso de almidón de papa como aditivo para lodos de perforación (2019)
The use of starches in the formulation of drilling fluids has been taking place since the 1930s, mainly as filter controllers and viscosity extenders. Corn and potato starches are the most used; moreover, the search for natural additives that could replace the commercial ones continues. Potato starch is a natural polymer whose amylose/amylopectin ratio and phosphorus content in the form of phosphate ester makes it superior to products such as corn, cassava, and plantain. The possibility of using potato starch, produced in Peru, as a drilling mud additive is contemplated as the country is considered one of the top 10 producers of this tuber worldwide. However, there is an absent industrialization of it, which represents an opportunity for potato and potato starch development in the country. This research evaluated the effect of potato starch and NaOH in the API filtrate of a water-based drilling fluid with mixed factorial design. According to the results obtained in this research, it was found that potato starch shows a better filter control property since with only 0.5 lb / bbl a decrease in filter loss was obtained with respect to a water-based Bentonitic sludge  with PAC-L. Likewise, it was proved that the PAC L can be replaced by the potato starch so that it can be used as a filter controller in a water-based mud, and to improve the rheological and viscosity properties of the same; contributing with this to the environmental sustainability, and generating a positive impact in the industry in the reduction of operational costs, and the industrial development of potato and its derivatives in Peru.